Comparative Study of Growth and Survival of Nile Tilapia (Oreochromis niloticus) on Different Feed Types (Nepalese Veterinary Journal, 2023)
This study aimed to compare the growth and survival of Nile tilapia (Oreochromis niloticus) fed with three different feed types: homemade feed (control), commercial feed, and earthworm-enriched feed. A total of 135 Nile tilapia with an average weight of 6.2 g and length of 6.5 cm were stocked in 9 hapas, with 15 fish per hapa. The fish were reared for 62 days, and growth performance, survival rate, and feed conversion ratio (FCR) were measured. The results showed that the final average weight and length of Nile tilapia fed with earthworm-enriched feed were higher than those fed with homemade and commercial feed. The highest mean weight gain (18.45 g) and mean length gain (4.7 cm) were observed in Nile tilapia fed with earthworm-enriched feed (T3R1). The FCR of Nile tilapia fed with earthworm-enriched feed (1.65) was lower than that of the other two groups. Moreover, the survival rate of Nile tilapia fed with earthworm-enriched feed was 100%, while the survival rate of Nile tilapia fed with homemade and commercial feed was 93.3% and 66.7%, respectively. In conclusion, earthworm-enriched feed showed superior performance in terms of growth and survival rate of Nile tilapia. This feed type can be considered as a potential alternative to the traditional homemade and commercial feed in the aquaculture industry. Further studies on the economic feasibility of using earthworm enriched feed for Nile tilapia are recommended.